Prevalence and antimicrobial susceptibility pattern of methicillin resistant Staphylococcus aureus isolates from Trinidad & Tobago - Monteil Michele; Swanston William; Kissoon Shivnarine; Akpaka Patrick (BMC, 2006)
Abstract Background Methicillin-resistant Staphylococcus aureus (MRSA) has become increasingly prevalent worldwide since it was first reported in a British hospital. The prevalence however, varies markedly in hospitals in the same country, and from one country to another. We therefore sought to document comprehensively the prevalence and antimicrobial susceptibility pattern of MRSA isolates in Trinidad and Tobago. Methods All Staphylococcus aureus isolates encountered in routine clinical specimens received at major hospitals in the country between 2000 and 2001 were identified morphologically and biochemically by standard laboratory procedures including latex agglutination test (Staphaurex Plus; Murex Diagnostics Ltd; Dartford, England); tube coagulase test with rabbit plasma (Becton, Dickinson & Co; Sparks, MD, USA), and DNase test using DNase agar (Oxoid Ltd; Basingstoke, Hampshire, England). MRSA screening was performed using Mueller-Hinton agar containing 6 μg oxacillin and 4% NaCl, latex agglutination test (Denka Seiken Co. Ltd, Tokyo, Japan) and E-test system (AB Biodisk, Solna, Sweden). Susceptibility to antimicrobial agents was determined by the modified Kirby Bauer disc diffusion method while methicillin MICs were determined with E-test system. Results Of 1,912 S. aureus isolates received, 12.8% were methicillin (oxacillin) resistant. Majority of the isolates were recovered from wound swabs (86.9%) and the least in urine (0.4%) specimens. Highest number of isolates was encountered in the surgical (62.3%) and the least from obstetrics and gynaecology (1.6%) facilities respectively. Large proportions of methicillin sensitive isolates are >85% sensitive to commonly used and available antimicrobials in the country. All MRSA isolates were resistant to ceftriaxone, erythromycin, gentamicin and penicillin but were 100% sensitive to vancomycin, rifampin and chloramphenicol. Conclusion There is a progressive increase in MRSA prevalence in the country but the present rate is still low in comparison to values in some other countries. Vancomycin is still the drug of choice for treating multidrug resistant MRSA infections. Further use of molecular studies to monitor the epidemiology of MRSA in these hospitals in the country is highly recommended too.